Somatosensory evoked potentials of the tibial nerve during the surgical decompression of thoracolumbar intervertebral disk herniation in dogs - Okuno, Seiichi; Katahira, Hirotaka; Orito, Kensuke (Frontiers in Veterinary Science, 2022)
This study aimed to identify the impact on spinal cord integrity and determine the electrophysiological safety level during surgery for thoracolumbar intervertebral disk herniation in dogs. A total of 52 dogs were diagnosed with thoracolumbar intervertebral disk herniation. The tibial nerve somatosensory evoked potential elicited on the scalp by stimulation of the tibial nerve was recorded during hemilaminectomy. Both the amplitude and latency of the somatosensory evoked potential were periodically registered, and the percentage changes from the preoperative control values (amplitude rate and latency rate) were calculated. When the multifidus muscles were retracted after removal from the spinous processes and vertebrae, the somatosensory evoked potential amplitude rate decreased in all dogs, while the latency rate increased in 33 dogs examined. The amplitude rate remained unchanged during the halting procedure, loosening retraction, and hemilaminectomy. After removing the disc material from the spinal canal, the amplitude rate was recovered. The somatosensory evoked potential latency increased when the multifidus muscles were retracted and recovered after multifidus muscles closure. There were no cases in which clinical signs deteriorated after surgery and all dogs could walk without assistance within 7 days post-operation. Spinal cord conduction is impaired by retraction of the multifidus muscles and improved by removal of disk materials. Thus, the alarm level of the functional deficit of the somatosensory tract in the thoracolumbar spinal cord for dogs seems to be 50% of the somatosensory evoked potential amplitude of the preoperative values.